2022
DOI: 10.1590/1807-3107bor-2022.vol36.0082
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of irradiance and radiant exposure on the polymerization and mechanical properties of a resin composite

Abstract: The objective of the present study was to evaluate the effect of irradiance and radiant exposure on the chemical-mechanical properties of a resin composite. A micro-hybrid resin composite (Clearfil AP-X, Kuraray) was investigated under two different irradiances: low (300 mW/cm 2 ) and high (800 mW/cm 2 ) and radiant exposures: 8 and 16 J/cm 2 . Four groups, named Low 8 J/cm 2 , High 8 J/cm 2 , Low 16 J/cm 2 , and High 16 J/cm 2 were tested, and their flexural strengths, elastic moduli, depths of cure, and degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Considering the irradiance (600 mW/cm 2 ) and the time of irradiation per section (20 s), the specimens received the following total radiant exposure: irradiance × time of irradiation: 15 mm × 1 mm–120 J/cm 2 , 10 mm × 1 mm–72 J/cm 2 , and 6 mm × 1 mm–24 J/cm 2 . Although there is no definite value, according to previous studies [ 63 , 64 , 65 ] a radiant exposure ranging from 16 to 20 J/cm 2 is enough to guarantee a suitable degree of conversion for a resin-based material. In the present study, for each resin-based restorative material, the DC% was not influenced by the specimen dimension ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the irradiance (600 mW/cm 2 ) and the time of irradiation per section (20 s), the specimens received the following total radiant exposure: irradiance × time of irradiation: 15 mm × 1 mm–120 J/cm 2 , 10 mm × 1 mm–72 J/cm 2 , and 6 mm × 1 mm–24 J/cm 2 . Although there is no definite value, according to previous studies [ 63 , 64 , 65 ] a radiant exposure ranging from 16 to 20 J/cm 2 is enough to guarantee a suitable degree of conversion for a resin-based material. In the present study, for each resin-based restorative material, the DC% was not influenced by the specimen dimension ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with a previous study that showed that the temperature rise was mainly determined by the radiant exposure. 45 The clinician should also be aware that delivering a low radiant exposure will compromise the mechanical properties of the restorations, 46,47 and can increase the material's toxicity. 47 For this in vitro study, the fluid flow through the pulp was adjusted to a flow rate of 0.026 mL/min based on previous studies.…”
Section: Discussionmentioning
confidence: 99%